Vertical transport through AlGaN barriers in heterostructures grown by ammonia molecular beam epitaxy and metalorganic chemical vapor deposition. (19th January 2017) - Browne, David A; Fireman, Micha N; Mazumder, Baishakhi; Kuritzky, Leah Y; Wu, Yuh-Renn; Speck, James S
Abstract: The results of vertical transport through AlGaN heterobarriers are presented for ammonia molecular beam epitaxy (NH3 -MBE) on c -plane GaN on sapphire templates and on m -plane bulk GaN substrates, as well as by metalorganic chemical vapor deposition (MOCVD) on m -plane bulk GaN substrates. Experiments were performed to determine the role of the AlGaN alloy as an effective barrier to vertical transport, which is an essential component of both optoelectronic and power electronic devices. The alloy composition, thickness, and doping levels of the AlGaN layers, as well as substrate orientation, were systematically varied to examine their influence on electron transport. Atom probe tomography (APT) was used to directly determine the alloy composition at the atomic scale to reveal the presence of random alloy fluctuations which provides insight into the nature of the observed transport.